Влияние электромагнитного экранирования на инфрадианную ритмику скорости движения планарий Dugesia tigrina - Ярмолюк, Н.С.; Чирский, Н.В.; Шехоткин, А.В. (Таврический медико-биологический вестник, 2010)
Виявлена інфрадіанна ритміка швидкості руху планарій Dugesia tigrina, яка включає наступні періоди: ≈2d,4; ≈2d,7; ≈3d,2; ≈3d,7; ≈4d,7; ≈5d,8; ≈8d,5; ≈11d,6; ≈12d,8. Електромагнітне екранування змінює інфрадіанну ритміку швидкості руху планарій, що виражається в виражених перебудовах спектрів потужності та зсуві фаз виділених періодів. Revealed infradian rhythmicity speeds of planarians Dugesia tigrina, which includes the following periods: ≈2d,4; ≈2d,7; ≈3d,2; ≈3d,7; ≈4d,3; 5d,8; ≈9d,1; ≈11d,6; ≈12d,8. It is shown that the electromagnetic shielding causes changes infradian rhythmicity speeds of planarians, which are expressed in changes of power spectra and phase shift of the beat.